The Death of Language: Listening to the Echoes (of Georges Bataille) in "Star Wars: Knights of the Old Republic II—The Sith Lords" - Hanuszkiewicz, Marcin (Text Matters: A Journal of Literature, Theory and Culture, 2020)
This article is, firstly, an analysis of Kreia, a character from the Star Wars: Knights of the Old Republic II—The Sith Lords video game, a character whose role in the game is pivotal: the conversations the player has with Kreia serve as the main narrative basis for the entire game experience. Secondly, on the basis of a collection of quotations from these conversations, this article juxtaposes Kreia and Georges Bataille. An intriguing variant of the blind seer trope is revealed in Kreia through studying the game’s poetics, in which a focus on the sense of hearing is discerned. Kreia and Bataille are compared in their understandings of the universe, and a similarity between their ulterior motives is discovered: both of them struggled against something which was considered to be an inextricable element of their respective universes.